Enabling Real-Time Search Of Medical Images Metadata At Scale - Basma AlKerm (2018)
Abstract
Contents
Thesis (M.A.)$1 (BNile University, Egypt, 2018 .s
"Includes bibliographical references"
Text in English, abstracts in English .
Keywords: Software Engineering; Dissertation, Academic